High-intensity focused ultrasound (HIFU) assisted by a rectal Foley catheter for the treatment of recurrent mucinous ovarian cancer: a case report and literature review - Guo, Xiaoyin; Liu, Wei; Zhou, Kun; Zhu, Hui; Pan, Lu; Feng, Chunping; Liu, Ling (Frontiers in Oncology, 2024)
​Mucinous ovarian cancer (MOC) is characterized by high malignancy, poor prognosis and a high recurrence rate. Surgical adjuvant chemotherapy is the main treatment for MOC. The recurrence rate of advanced mucinous ovarian cancer following surgery is significantly high, with limited efficacious treatment options available. Moreover, chemotherapy alone results in low sensitivity in this context. High-intensity focused ultrasound (HIFU) not only efficiently ablates targeted tumor lesions but also elicits an immune response within the body and increases tumor cell susceptibility to drugs, thus increasing therapeutic effectiveness. We report a case of recurrent mucinous ovarian cancer treated with HIFU combined with chemotherapy, which effectively controlled tumor growth and prolonged patient survival. High-intensity focused ultrasound in combination with chemotherapy for the treatment of recurrent and surgically difficult ovarian cancer could provide new treatment strategies.